Changes In School Organizational Culture (Case Study State Junior High School 1 Pematangsiantar) - Enjel O.Simanjutak; Joharis Lubis; Nathanael Sitanggang (CV. Inara, 2021)
The purpose of this study is to describe how organizational cultural changes occur in the school environment, especially regarding organizational relationships with respect to the change of principals. Schools are one of the stakeholders in the world of education that have an important role in shaping the character and abilities of students. Schools carry out the learning process cannot be separated from the role of teachers to achieve goals. This type of research is a qualitative research using a case study approach. Data collection techniques used by observation, interviews, documentation. The communication approach and its implementation in educational leadership, namely: Leadership Theory, Human Relations Approach, Communication Approach as an Organizing Process, Approach to Organizational Structure and Functions. form synergistic cooperation to members by assigning tasks and responsibilities cooperatively and coordinatively in an effort to achieve school goals.